Bipolar Disorder in Older Age Patients - Lehmann, Susan W.; Forester, Brent P. (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive but practical understanding of the clinical approach to evaluating and caring for older people with bipolar disorder. Aspects of aging that impact the diagnosis, clinical course, and management of bipolar disorder are explained; in particular, attention is drawn to the implications of comorbidities and medical complexity for the psychiatric care of older individuals with the disorder. On the other hand, similarities to treatment in younger patients are also identified. The coverage includes thorough review of current research in the field. Clinical case vignettes are used throughout to highlight practical points, and each chapter includes "clinical pearls" that summarize key points for the clinician. The book closes by examining anticipated research directions and the future needs of this patient population. Bipolar Disorder in Older Age Patients will be an ideal update for the practicing community or geriatric psychiat rist working with older patients with bipolar disorder.